Schelling's Critical View on Leibniz's Notion of Evil - Petrou, Veroniki (Conatus - Journal of Philosophy, 2018)
This article attempts to present the divergences, as well as the possible approaches, of both Schelling's and Leibnitz's philosophical positions concerning the concept of evil. The whole discussion is carried out in the light of a hypothetical dialogue, which is essentially based on Schelling's critique of the fundamental arguments of Leibniz's Theodicy.